Pengembangan Sistem Informasi Monitoring Program Kerja Berbasis Android pada Fakultas Teknik Universitas Nurul Jadid - Fathorazi Nur Fajri; Kamil Malik; Halimatus Sa'diya (Universitas Nurul Jadid, 2020)
UNUJA has a faculty where each faculty has a work program. Until now, the Faculties and Work Units still have difficulties in monitoring the report benchmarks in achieving targets when doing work. So that the leadership or the Dean has difficulty in monitoring the results of the completion of the work program. From the existing problems, the researcher took a theme about